Preparation method and application of sulfonate grafted aramid nanofiber Janus membrane
Patent Information
- Application Number
- CN202611016690.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-09
AI Technical Summary
然而,其实际应用仍受限于两大关键问题:一是可溶性多碘化物中间产物(主要为I3-、I5-)在浓度梯度驱动下从正极区域扩散、穿过隔膜迁移至锌负极表面,与锌金属发生不可逆化学反应,导致活性物质持续损失和严重自放电,这一现象被称为多碘化物穿梭效应,是导致锌碘电池容量快速衰减与循环寿命受限的根源性挑战;二是锌负极界面稳定性较差,锌离子不均匀沉积会导致锌枝晶生长,容易刺穿隔膜导致电池短路,而且,由于锌负极电位低于析氢电位,会导致水分解产生氢气,即析氢反应,严重消耗电解液同时内压聚集导致电池失效
本发明首次在锌碘电池领域采用ANF-g-SSNa化学接枝与半接枝Janus不对称结构设计。相比于现有的全表面均质磺化改性隔膜(如磺化纤维素隔膜、ACE膜等),本发明的半接枝Janus结构在功能化侧的高密度-SO3-基团通过静电排斥阻隔多碘化物穿梭的同时,未功能化侧的原始ANF层保留了高孔隙率的三维纳米纤维网络,离子传输阻力小,有效克服了均质改性因孔道堵塞导致的高倍率下离子传导性能下降的缺陷。通过采用化学接枝而非物理涂覆实现功能化,功能层结合牢固。本发明的SSNa通过自由基聚合以共价键形式接枝于ANF表面,不仅避免了物理涂覆层在长期循环中因溶胀、电化学应力导致的剥离脱落,而且由于化学接枝过程发生在ANF的表面纤维而非整个膜体,功能化层的引入位置可控,接枝率可通过单体浓度和反应条件精确调控。本发明的Janus隔膜各项指标满足电池组装和长期循环的机械强度要求。本发明采用顺序真空抽滤法构建非对称结构,无需精密掩模、多步涂覆或等离子体处理等复杂工艺,工艺窗口宽、设备要求低、批次稳定性好,有利于工业化放大生产。同时,ANF水分散液和ANF-g-SSNa水分散液均具有良好的胶体稳定性,为长期储存和工程化应用奠定了基础。
Smart Images

Figure CN122576603B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aqueous zinc-ion battery separator technology, specifically to a method for preparing and applying a sulfonate-grafted modified aramid nanofiber Janus separator. Background Technology
[0002] Aqueous zinc-iodine batteries benefit from the high theoretical capacity (820 mAh·g) of the zinc anode. -1 The suitable redox potential for the iodine cathode (approximately 1.3V vs. Zn) 2+ The intrinsic safety of aqueous electrolytes (such as Zn) and other electrolytes makes them strong contenders for next-generation large-scale, low-cost energy storage devices. However, their practical application is still limited by two key issues: one is the presence of soluble polyiodide intermediates (mainly I3). - I5 - Driven by the concentration gradient, zinc ions diffuse from the positive electrode region, migrate through the separator to the zinc negative electrode surface, and undergo an irreversible chemical reaction with zinc metal, leading to continuous loss of active material and severe self-discharge. This phenomenon is known as the polyiodide shuttle effect, which is the root cause of the rapid capacity decay and limited cycle life of zinc-iodine batteries. Secondly, the zinc negative electrode interface has poor stability. Uneven deposition of zinc ions can lead to the growth of zinc dendrites, which can easily puncture the separator and cause a short circuit in the battery. Moreover, since the zinc negative electrode potential is lower than the hydrogen evolution potential, it can cause water decomposition to produce hydrogen gas, i.e., the hydrogen evolution reaction, which severely consumes electrolyte and causes internal pressure accumulation, leading to battery failure.
[0003] In aqueous zinc-iodine batteries, although the separator does not directly participate in the electrochemical reaction, its physicochemical properties play a decisive role in suppressing the polyiodide shuttle effect and regulating the interfacial behavior of the zinc anode. Traditional commercial separators (such as glass fiber separators, typically >1 μm) have large pore sizes, inert surfaces, and lack ion selectivity. These structural defects prevent them from effectively blocking I3. - / I5 - Soluble polyiodide anions migrate from the positive electrode to the negative electrode. I3 - The kinetic diameter is only about 5.14 Å. Facing the macroscopic pores of the GF separator (greater than 1 μm), it experiences almost no sieving resistance, leading to severe self-discharge and rapid capacity decay in the battery. Meanwhile, the GF separator... 2+ The lack of guiding effect in deposition easily leads to uneven electric field distribution on the electrode surface, making it difficult to suppress side reactions such as hydrogen evolution and easily inducing zinc dendrite growth. In addition, GF membranes also suffer from low mechanical strength, inability to resist zinc dendrite penetration, large thickness (about 600 μm), and high cost, making their application bottlenecks increasingly prominent.
[0004] In recent years, researchers have gradually developed various functionalized membranes to address the aforementioned problems. Among them, sulfonated cellulose membranes introduce sulfonate groups (-SO3) onto a cellulose substrate. - Significant results were achieved by utilizing electrostatic repulsion to block polyiodide shuttle and regulate zinc ion transport. For example, the paper titled "Ion-Sieving Effect Enabled by Sulfonation of Cellulose Separator Realizing Dendrite-Free Zn Deposition" discloses a sulfonated cellulose membrane that introduces -SO3... - The functional groups achieve an ion sieving effect, enabling Zn / / Zn symmetric cells to operate at 4 mAh·cm⁻¹. -2 It can operate stably for 1200 hours and maintain a lifespan of 400 hours even at a maximum discharge depth of 68.3%. Furthermore, a paper titled "Simultaneous inhibition of zn dendrites and polyiodide ions shuttle effect by an anion concentrated electrolyte membrane for long-lifespanaqueous zinc-iodine batteries" discloses an anion concentrated electrolyte membrane (ACE membrane). Its polymer backbone is rich in sulfonic acid groups, which can both block polyiodide shuttles through electrostatic repulsion and guide Zn... 2+ A stable negative electrode flux ultimately achieves a long lifespan of 3700 hours for the zinc-iodine battery. However, most of these sulfonation modification strategies are full-surface homogeneous modifications—that is, introducing high-density sulfonate groups across the entire membrane surface. This homogeneous modification has the following problems: First, although full-surface sulfonation can introduce high-density -SO3 groups... - While using functional groups to enhance ion selectivity, this method can easily clog the effective pores within the membrane, leading to Zn... 2+ The migration path of iodine dendrites becomes longer, leading to decreased ionic conductivity and deterioration of mechanical properties. Secondly, the mechanical strength of cellulose-based membranes significantly decreases after the introduction of sulfonate groups due to the disruption of the hydrogen bond network. Although ACE membranes maintain certain mechanical properties using a rigid polymer backbone, homogenization inevitably introduces a large number of flexible polymer segments, reducing the membrane's resistance to zinc dendrite penetration. Furthermore, while pursuing high sulfonate group density to enhance iodine barrier properties, homogenization inevitably sacrifices ionic conductivity, a long-standing technical dilemma in this field.
[0005] In recent years, Janus-type membranes, also known as bilaterally asymmetric functional membranes, have provided a new approach to resolving the aforementioned contradictions. For example, the team of Zhao Jinbao and Yang Yang at Xiamen University constructed a Janus membrane based on cation exchange resin and Fe nanoparticle-modified single-walled carbon nanotubes (SWCNTs). This membrane utilizes the -SO3- of the cation exchange resin... - Group attraction Zn 2+ It repels polyiodide anions, while the other side is loaded with Fe nanoparticles to anchor and catalyze the conversion of polyiodides, achieving 2500 hours of cycling and 3.6 mAh·cm⁻¹. -2 The high areal capacity is achieved. However, although this scheme realizes the Janus structure, it functionalizes both sides of the SWCNT substrate—one side is a cation exchange resin, and the other side is a Fe@SWCNT functional layer. While the dual-sided functionalization design is effective in suppressing polyiodine shuttle, the Fe nanoparticle functional layer on the other side, while achieving catalytic conversion of polyiodides, also causes some blockage of the ion transport channels, increasing the Zn content. 2+ The resistance to transmembrane transport affects the overall performance of the membrane at high rates. Moreover, SWCNTs, as a membrane substrate, have poor film-forming properties compared to nanofiber materials, requiring complex loading processes and making it difficult to form a self-supporting membrane. Furthermore, the cation exchange resin is physically coated onto the SWCNT surface, resulting in weak interfacial bonding between the functional layer and the substrate. During long-term cycling, it is prone to peeling and detachment due to electrochemical stress and electrolyte swelling, leading to a decrease in iodine barrier capacity. Therefore, this approach remains difficult to scale up for mass production. Summary of the Invention
[0006] The first objective of this invention is to provide a method for preparing a Janus sulfonate-grafted modified aramid nanofiber membrane, and the second objective of this invention is to provide an application of a Janus sulfonate-grafted modified aramid nanofiber membrane.
[0007] The first objective of this invention is achieved by the following technical solution: A method for preparing a Janus membrane made of sulfonate-grafted modified aramid nanofibers includes the following steps: S1. Preparation of aqueous dispersion of aramid nanofibers; S2. The aramid nanofiber aqueous dispersion prepared in S1 is mixed with sodium p-styrene sulfonate, initiator and reducing agent, and a free radical polymerization grafting reaction is carried out under anaerobic conditions. After washing and redispersing, a modified dispersion is obtained. S3. Using a sequential vacuum filtration method, the modified dispersion obtained in S2 is first filtered into a membrane to form the first layer; then, the aramid nanofiber aqueous dispersion obtained in S1 is filtered on the first layer to form the second layer; after drying and peeling, the sulfonate-grafted modified aramid nanofiber Janus membrane is obtained.
[0008] Furthermore, S1 includes the following steps: S11. Disperse poly(p-phenylene terephthalamide) in a mixture containing dimethyl sulfoxide, KOH, and deionized water; stir at 50-60°C for 4-12 hours to form a concentration of 2 mg / ml. -1 A uniform, deep red ANF / DMSO dispersion; S12. Add deionized water as a proton donor to the ANF / DMSO dispersion and continue stirring for 1 hour to complete the deprotonation reaction. S13. The mixed solution obtained from the deprotonation reaction is subjected to vacuum-assisted filtration to obtain a mixed gel. S14. Repeatedly add ethanol and deionized water to the mixture gel for washing and filtration to purify the mixture gel. S15. Redisperse the purified gel in deionized water under stirring, and adjust the concentration to 2 mg / ml. -1 A stable ANF aqueous dispersion, namely aramid nanofiber aqueous dispersion, was obtained.
[0009] Furthermore, in S11, the ratio of poly(p-phenylene terephthalamide): dimethyl sulfoxide: KOH: deionized water is 1g: 500ml: 1.5g: 20ml.
[0010] Furthermore, S2 includes the following steps: S21. Take the aqueous dispersion of aramid nanofibers, remove most of the water by vacuum filtration, and obtain ANF colloid; S22. Transfer the ANF colloid to a light-proof container, and add the reducing agent, initiator and sodium p-styrene sulfonate monohydrate in sequence. S23. Place the light-proof container in a vacuum drying oven and repeatedly evacuate and purge with nitrogen three times to completely remove oxygen. After sealing, stir in a water bath at 50~60℃ for 2~6 hours to obtain crude ANF-g-SSNa product. S24. The crude ANF-g-SSNa product was washed multiple times with a large amount of deionized water, and then ultrasonically redispersed to adjust the concentration to 2 mg / mL. -1 A stable ANF-g-SSNa aqueous dispersion, i.e., modified dispersion, was obtained.
[0011] Furthermore, the mass ratio of aramid nanofibers to sodium p-styrene sulfonate monohydrate in the aramid nanofiber aqueous dispersion is 1:(1~5).
[0012] Furthermore, the initiator is ammonium persulfate, and the reducing agent is sodium bisulfite.
[0013] Furthermore, the mass ratio of aramid nanofibers to initiator in the aramid nanofiber aqueous dispersion is 1:(0.1~1), and the mass ratio of aramid nanofibers to reducing agent in the aramid nanofiber aqueous dispersion is 1:(0.5~1.5).
[0014] Furthermore, S3 includes the following steps: S31. Mix the modified dispersion with deionized water, ultrasonically disperse for 10 min, pour into a vacuum filtration device, and vacuum filter to form an ANF-g-SSNa layer. S32. Mix the aramid nanofiber aqueous dispersion with deionized water, ultrasonically disperse for 10 minutes, and then pour it into the filtration device described in S31. Continue filtration above the ANF-g-SSNa layer to form an ANF layer. After vacuum filtration is completed, a composite membrane is formed. Take the composite membrane and the filter membrane out of the filtration device together. S33. After the composite membrane and the filter membrane are vacuum dried together at 60°C for 12 hours, the filter membrane is peeled off to obtain the ANF / ANF-g-SSNa Janus membrane, namely the sulfonate grafted modified aramid nanofiber Janus membrane, wherein the total thickness of the sulfonate grafted modified aramid nanofiber Janus membrane is 5~20μm.
[0015] Furthermore, the volume ratio of the modified dispersion taken in S31 to the aramid nanofiber aqueous dispersion taken in S32 is 1:(1~2.5).
[0016] The second objective of this invention is achieved by the following technical solution: The sulfonate-grafted modified aramid nanofiber Janus separator prepared by the method for preparing the sulfonate-grafted modified aramid nanofiber Janus separator according to the first objective of the present invention is used to prepare a zinc-iodine battery, wherein the ANF-g-SSNa layer faces the positive electrode side and the ANF layer faces the negative electrode side.
[0017] The above assembly method allows the sulfonate functional layer to directly face the positive electrode side, generating a large amount of polyiodides, thus achieving source interception; the ANF layer faces the negative electrode side, utilizing its high-porosity three-dimensional network to provide Zn. 2+ It provides a low-resistance channel for transport to the zinc anode, while utilizing its hydrophilicity and amide groups to regulate the uniform deposition of zinc ions and inhibit dendrite growth.
[0018] Advantages of this invention: This invention is the first in the field of zinc-iodine batteries to employ an ANF-g-SSNa chemical grafting and semi-grafted Janus asymmetric structure design. Compared to existing homogeneous sulfonated modified membranes (such as sulfonated cellulose membranes, ACE membranes, etc.), the semi-grafted Janus structure of this invention features a high density of -SO3 on the functionalized side. -While the functionalized groups block the shuttle passage of polyiodides through electrostatic repulsion, the original ANF layer on the unfunctionalized side retains a high-porosity three-dimensional nanofiber network with low ion transport resistance, effectively overcoming the defect of decreased ion conductivity at high rates due to pore blockage caused by homogeneous modification. Functionalization is achieved through chemical grafting rather than physical coating, resulting in a strong bond between the functional layers. The SSNa of this invention is grafted onto the ANF surface via free radical polymerization in a covalent manner. This not only avoids the peeling and detachment of the physical coating layer due to swelling and electrochemical stress during long-term cycling, but also allows for controllable introduction of the functionalized layer because the chemical grafting process occurs on the surface fibers of the ANF rather than the entire membrane. The grafting rate can be precisely controlled by monomer concentration and reaction conditions. The Janus separator of this invention meets the mechanical strength requirements for battery assembly and long-term cycling. This invention uses a sequential vacuum filtration method to construct an asymmetric structure, eliminating the need for complex processes such as precision masks, multi-step coating, or plasma treatment. It offers a wide process window, low equipment requirements, and good batch stability, which is beneficial for industrial-scale production. Meanwhile, both ANF aqueous dispersion and ANF-g-SSNa aqueous dispersion exhibit good colloidal stability, laying the foundation for long-term storage and engineering applications. Attached Figure Description
[0019] Figure 1 In the image, (a) is the SEM surface morphology of the ANF membrane at the 10 μm scale, (b) is the SEM surface morphology of the ANF membrane at the 1 μm scale, (c) is the SEM surface morphology of the ANF-g-SSNa membrane at the 10 μm scale, and (d) is the SEM surface morphology of the ANF-g-SSNa membrane at the 1 μm scale. Figure 2 Fourier transform infrared (FT-IR) spectra of ANF membrane and ANF-g-SSNa membrane; Figure 3 XRD patterns of ANF membrane and ANF-g-SSNa membrane; Figure 4 XPS full spectrum of ANF membrane and ANF-g-SSNa membrane; Figure 5 In the figure, (a) is the C 1s high-resolution XPS spectrum of the ANF membrane, and (b) is the C 1s high-resolution XPS spectrum of the ANF-g-SSNa membrane. Figure 6 In the figure, (a) is the N 1s high-resolution XPS spectrum of the ANF membrane and the ANF-g-SSNa membrane, (b) is the O 1s high-resolution XPS spectrum of the ANF membrane and the ANF-g-SSNa membrane, and (c) is the S 2p high-resolution fine spectrum of the ANF-g-SSNa membrane. Figure 7In the image, (a) is a cross-sectional SEM image of the ANF / ANF-g-SSNa membrane, where (i) is a magnified view of the ANF-g-SSNa side and (ii) is a magnified view of the ANF side; (b) is an elemental distribution image of the ANF / ANF-g-SSNa membrane. Figure 8 For Zn / / Zn symmetric cells at 1 mA·cm -2 1mAh·cm -2 SEM images of zinc sheet surfaces after cycling under the specified conditions: (a) ANF membrane; (b) ANF-g-SSNa membrane; (c) Zinc sheet on the ANF side of the Janus-type membrane; (d) Zinc sheet on the ANF-g-SSNa side of the Janus-type membrane. Figure 9 For Zn / / Zn symmetric cells using different separators at 1 mA·cm -2 1mAh·cm -2 X-ray diffraction (XRD) pattern of zinc sheet after cycling; Figure 10 In the figure, (a) is 1 mA·cm -2 1mAh·cm -2 Time-voltage curves of Zn / / Zn symmetric cells using ANF, ANF-g-SSNa and ANF / ANF-g-SSNa membranes under the conditions, (b) is a local time-voltage plot from 20 to 30 h, and (c) is a local time-voltage plot from 2310 to 2360 h. Figure 11 1 mA·cm -2 1mAh·cm -2 Time-voltage curves of Zn / / Zn symmetric cells using GF membrane under the specified conditions; Figure 12 In the diagram, (a) represents the temperature at 2 mA·cm⁻¹. -2 2mAh·cm -2 Time-voltage curves of Zn / / Zn symmetric cells using GF, ANF, ANF-g-SSNa and ANF / ANF-g-SSNa films under the conditions, (b) are local time-voltage plots for 100-114h, 318-325h, 787-805h and 1450-1470h. Figure 13 Voltage-time curves of Zn / / Zn symmetric cells using different separators under multi-current-density step tests; Figure 14 In the figure, (a) represents the temperature at 5 mA·cm⁻¹ -2 2.5mAh·cm -2(a) Time-voltage curves of Zn / / Zn symmetric cells using GF, ANF, ANF-g-SSNa, and ANF / ANF-g-SSNa films under the specified conditions; (b) Local time-voltage curves for 740–840 h; (c) Time-voltage curves at 10 mA·cm⁻¹. -2 5 mAh·cm -2 Time-voltage curve under the given conditions; Figure 15 Optical photographs of iodine shuttle visualization in a U-shaped electrolytic cell for 24 h with different diaphragms; Figure 16 Schematic diagrams illustrating the regulatory mechanisms of different diaphragms on the shuttle effect of polyiodine substances: (a) GF; (b) ANF; (c) ANF-g-SSNa; (d) ANF / ANF-g-SSNa; Figure 17 Self-discharge capacity retention of batteries using GF, ANF, ANF-g-SSNa and ANF / ANF-g-SSNa separators; Figure 18 In the figure, (a) shows the cells using GF, ANF, ANF-g-SSNa, and ANF / ANF-g-SSNa separators at current densities starting from 0.2 A·g -1 Gradually increase to 4 A·g -1 It then dropped back to 0.2 A·g -1 (a) The specific capacity change curve during the process; (b) The GCD curve of the first charge-discharge cycle of the battery using ANF / ANF-g-SSNa separator at different current densities. Figure 19 For a current density of 0.1 A·g -1 Long-cycle curves of ANF / ANF-g-SSNa, ANF-g-SSNa, ANF and GF membranes under certain conditions; Figure 20 For a current density of 1 A·g -1 Long-cycle curves of ANF / ANF-g-SSNa, ANF-g-SSNa, ANF and GF membranes under certain conditions. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Example 1 A method for preparing a Janus membrane made of sulfonate-grafted modified aramid nanofibers includes the following steps: S1. Preparation of an aqueous dispersion of aramid nanofibers, specifically including the following steps: S11. Disperse 1g of poly(p-phenylene terephthalamide) (PPTA) in a mixture containing 500ml of dimethyl sulfoxide (DMSO), 1.5g of KOH, and 20ml of deionized water; stir at 50℃ for 4h to form a total concentration of 2 mg / ml of poly(p-phenylene terephthalamide), dimethyl sulfoxide, and KOH. -1 A uniform, deep red ANF / DMSO dispersion; S12. Add 250 ml of deionized water to the ANF / DMSO dispersion as a proton donor, and continue stirring for 1 h to complete the deprotonation reaction. S13. The mixed solution obtained from the deprotonation reaction is subjected to vacuum-assisted filtration to obtain a mixed gel. S14. Repeatedly add ethanol and deionized water to the mixture gel for washing and filtration to completely remove residual DMSO and potassium hydroxide in the system and purify the mixture gel. S15. Redisperse the purified gel in deionized water under stirring, and adjust the concentration to 2 mg / ml. -1 A stable ANF aqueous dispersion, namely aramid nanofiber aqueous dispersion, was obtained. The dispersion exhibited a significant Tyndall effect, indicating the formation of uniformly dispersed nanoscale micelles.
[0022] S2. The aramid nanofiber aqueous dispersion prepared in S1 is mixed with sodium p-styrene sulfonate, an initiator, and a reducing agent, and a free radical polymerization grafting reaction is carried out under anaerobic conditions. After washing and redispersing, a modified dispersion is obtained, specifically including the following steps: S21. Take 50 ml of aramid nanofiber aqueous dispersion (containing 100 mg ANF), remove most of the water by suction filtration to obtain ANF colloid; S22. Transfer the ANF colloid to a brown sieve bottle, and add 100 mg of sodium bisulfite (NaHSO3), 60 mg of ammonium persulfate (APS), and 400 mg of sodium p-styrene sulfonate monohydrate (SSNa) in sequence. H2O); S23. Place the brown filament bottle in a vacuum drying oven and repeatedly evacuate and purge with nitrogen three times to completely remove oxygen. After sealing, stir in a 55°C water bath and perform the grafting reaction for 4 hours to obtain the crude product ANF-g-SSNa. S24. Wash the crude ANF-g-SSNa product three times with plenty of deionized water to remove unreacted SSNa monomers and residual initiator. After ultrasonic redispersion, adjust the concentration to 2 mg / mL. -1A stable ANF-g-SSNa aqueous dispersion, i.e., modified dispersion, was obtained.
[0023] S3. Using a sequential vacuum filtration method, the modified dispersion obtained in S2 is first filtered to form a membrane, forming the first layer; then, the aramid nanofiber aqueous dispersion obtained in S1 is further filtered on the first layer to form the second layer; after drying and peeling, the sulfonate-grafted modified aramid nanofiber Janus membrane is obtained. Specifically, S3 includes the following steps: S31. Mix 5 ml of ANF-g-SSNa dispersion with 25 ml of deionized water, sonicate for 10 min to allow the SSNa chain segments to fully extend, pour into a vacuum filtration device, and vacuum filter to form an ANF-g-SSNa layer with a thickness of about 5 μm. S32. Mix 5 ml of ANF aqueous dispersion with 25 ml of deionized water, sonicate for 10 min, and then pour into the vacuum filtration device described in S31. Continue vacuum filtration above the ANF-g-SSNa layer to form an ANF layer with a thickness of about 5 μm. After vacuum filtration is completed, a composite membrane with a total thickness of about 10 μm is formed. Take the composite membrane and the filter membrane out of the vacuum filtration device together. S33. After drying the composite membrane together with the filter membrane under vacuum at 60°C for 12 hours, gently peel off the filter membrane to obtain the ANF / ANF-g-SSNa Janus membrane, which is a sulfonate-grafted modified aramid nanofiber Janus membrane.
[0024] Example 2 The only difference between this embodiment and Example 1 is that in S2, the amount of SSNa·H2O is changed to 200 mg, the amount of APS is changed to 30 mg, and the amount of NaHSO3 is changed to 50 mg. In S23, the reaction time is extended to 6 hours. All other steps and parameters are the same as in Example 1.
[0025] Example 3 The difference between this embodiment and Example 1 is that in S2, the amount of SSNa·H2O is changed to 500 mg, the amount of APS is changed to 75 mg, and the amount of NaHSO3 is changed to 125 mg. In S23, the reaction temperature is increased to 60°C, and the reaction time is shortened to 3 h. The remaining steps and parameters are the same as in Example 1.
[0026] Application Example 1 The sulfonate-grafted modified aramid nanofiber Janus membrane prepared in Example 1 was used to assemble a Zn / / Zn symmetric cell, wherein: Positive and negative electrodes: both use zinc foil with a diameter of 14 mm and a thickness of 100 μm; Electrolyte: 100 μl 2M Zn(CF3SO3)2 aqueous solution.
[0027] Separator: The sulfonate-grafted modified aramid nanofiber Janus separator prepared in Example 1 has a diameter of 16 mm; and the ANF-g-SSNa layer faces the positive electrode side and the ANF layer faces the negative electrode side.
[0028] Application Example 2 The sulfonate-grafted modified aramid nanofiber Janus membrane prepared in Example 1 was used to assemble a Cu / / Zn half-cell, wherein: Positive electrode: 14mm diameter copper foil, 100μm thickness; Negative electrode: Zinc foil with a diameter of 14 mm and a thickness of 100 μm; Diaphragm and electrolyte: Same as in application example 1.
[0029] Comparative Example 1 The only difference between this comparative example and application example 1 is that the sulfonate-grafted modified aramid nanofiber Janus membrane prepared in example 1 is replaced with the original ANF membrane.
[0030] The original ANF membrane was prepared as follows: 10 mL of the ANF aqueous dispersion prepared in S1 of Example 1 was mixed with 50 mL of deionized water, ultrasonically dispersed for 10 minutes, and then poured into a vacuum filtration device to form a membrane. The membrane was vacuum dried at 60°C for 12 hours and then peeled off to obtain a pure ANF self-supporting membrane with a thickness of about 10 μm. This membrane was not subjected to any sulfonation or functionalization treatment.
[0031] Comparative Example 2 The only difference between this comparative example and application example 1 is that the sulfonate-grafted modified aramid nanofiber Janus membrane prepared in example 1 is replaced with an ANF-g-SSNa homogeneous sulfonated membrane.
[0032] The preparation method of the ANF-g-SSNa homogeneous sulfonated membrane is as follows: 10 mL of the ANF-g-SSNa aqueous dispersion prepared in S2 of Example 1 is mixed with 50 mL of deionized water, ultrasonically dispersed for 10 minutes, and then poured into a vacuum filtration device to form a membrane. After vacuum drying at 60°C for 12 hours, an ANF-g-SSNa homogeneous functional membrane with a thickness of about 10 μm is obtained after peeling. Both sides contain high-density sulfonate groups.
[0033] Comparative Example 3 The only difference between this comparative example and application example 1 is that the sulfonate-grafted modified aramid nanofiber Janus membrane prepared in example 1 is replaced with a commercially available Whatman glass fiber membrane GF / B with a pore size of about 1 μm and a thickness of about 260 μm.
[0034] Experimental Example This experimental example systematically characterized the basic physicochemical properties and morphology of the diaphragms used in Example 1 and Comparative Examples 1-3, as detailed below: 1. Morphology and structure of the diaphragm Figure 1 Images (a)-(d) show the surface SEM morphology of the membrane before and after grafting. It can be seen that the ANF membrane exhibits a typical three-dimensional interpenetrating nanofiber network structure with uniform fiber distribution and continuous, interconnected pores, which is beneficial for sufficient electrolyte wetting and rapid ion transport. After grafting with SSNa, the resulting ANF-g-SSNa membrane, at low magnification (10 μm scale), Figure 1 (c) The surface is noticeably denser and smoother, and the pore structure of the original fiber network is almost invisible, indicating that the polymer graft layer effectively covers the fiber gaps. Further observation at high magnification (1 μm scale)... Figure 1 (d) The complete nanofiber framework can still be clearly distinguished, and there are no phenomena such as fiber breakage or membrane structure collapse. This shows that the free radical polymerization reaction conditions used in this invention are mild, and effectively maintain the structural integrity of the ANF substrate while achieving efficient functionalization.
[0035] To further verify the grafting effect, FTIR spectral analysis was also performed, such as... Figure 2 As shown, the ANF-g-SSNa membrane at 1150 cm⁻¹ -1 A new absorption peak appeared at this point, corresponding to -SO3 in SSNa. - The symmetric stretching vibration mode of the group confirmed that SSNa was successfully grafted onto the ANF surface.
[0036] Figure 3 The XRD pattern shown indicates that the ANF membrane exhibits a broad and diffuse diffraction peak at 2θ≈20.22°, corresponding to the π-π stacking distance of the aramid molecular chains (d≈0.44nm), indicating that it is a typical semi-crystalline polymer. In the XRD pattern of the ANF-g-SSNa membrane grafted with SSNa, the intensity of this characteristic peak is slightly weakened, the peak position shifts slightly to a higher angle (2θ≈21°), and the peak shape is further broadened, without the appearance of new sharp diffraction peaks. This suggests that the grafting reaction did not destroy the main chain structure of ANF, nor did it introduce a highly ordered crystalline phase. Instead, it formed a grafted layer dominated by amorphous SSNa, consistent with the surface densification observed by SEM. This result further confirms that the free radical grafting process maintains the basic molecular configuration of the ANF matrix while achieving functionalization.
[0037] Figure 4The XPS full spectrum shown indicates that characteristic C 1s, N 1s, and O 1s signals were detected in both the ANF membrane and the ANF-g-SSNa membrane, originating from the benzene ring / amide groups (-CO-NH-) in the aramid backbone and the oxygen-containing species adsorbed on the surface, respectively. A significant S 2p signal was detected only in the ANF-g-SSNa membrane, while no sulfur was observed in the ANF membrane. This result further confirms the successful introduction of sodium styrene sulfonate (SSNa) onto the ANF surface.
[0038] Figure 5 (a) High-resolution XPS spectrum of C 1s of pure ANF is shown. Three main carbon species can be identified by peak fitting: the peak with a binding energy of 284.8 eV belongs to the CC / C=C structure in the aromatic ring; the peak at 285.8 eV corresponds to the CN group in the amide bond; and the peak at 287.9 eV originates from the amide carbonyl group (OC=O)
[80] . The above characteristic peaks are highly consistent with the typical chemical structure of aramid (PPTA) molecular chain, which confirms that the prepared ANF substrate maintains a complete molecular skeleton and a stable amide bond structure. Figure 5 (b) is the C1s high-resolution spectrum of the ANF-g-SSNa membrane. Compared with the ANF membrane, Figure 5 (b) A new characteristic peak appears at 285.1 eV, which can be attributed to the CS / CO bond in the grafted sodium p-styrene sulfonate (SSNa) segment, confirming the successful grafting of sodium p-styrene sulfonate (SSNa) onto the ANF surface. Furthermore, the peaks originally attributed to CN (285.84 eV) and OC=O (288.07 eV) have shifted, indicating that the grafting reaction caused some disturbance to the local chemical environment, but the main chain amide bond structure remained intact without significant damage. This result further confirms the feasibility of achieving surface functionalization through chemical grafting without destroying the substrate structure.
[0039] Figure 6(ac) shows the high-resolution XPS spectra of the ANF-g-SSNa membrane at N 1s, O 1s, and S 2p. In the N 1s spectrum, a new N-S bond peak appears at 399.22 eV for the ANF-g-SSNa membrane, indicating a covalent bond between SSNa and ANF. In the O 1s spectrum, the ANF-g-SSNa membrane shows a peak at 533.76 eV. A new characteristic peak at 168.5 eV, belonging to the sulfonate group (O=S=O), confirms the successful introduction of the sulfonate group. Compared with the ANF membrane, the peak intensity of the hydrogen-bonded carbonyl group (SSNa) after grafting is significantly weakened or even disappears, the binding energy shifts to lower energies, and the peak area ratio of free carbonyl group (C=Ofree) increases significantly. This change indicates that the sodium p-styrene sulfonate (SSNa) segment grafted onto the ANF surface disrupts part of the original intermolecular hydrogen bond network (C=O···HN) on the ANF surface, causing some carbonyl groups that originally participated in hydrogen bonding to become free. This result confirms the successful grafting of SSNa and its effective regulation of the microstructure of the ANF surface from a chemical environment perspective. The S 2p spectrum at 168.5 eV shows a typical -SO3- - The (S 2p3 / 2) signal further confirmed the presence of sulfonate groups, and no obvious signal was detected in this region by the ANF membrane.
[0040] In summary, SSNa was successfully grafted onto the surface of ANF via free radical polymerization, which not only preserved the high mechanical strength and good pore structure of ANF, but also endowed it with excellent iodine barrier properties, laying the foundation for the subsequent construction of asymmetric functional membranes.
[0041] 2. Diaphragm design and mechanical performance testing Figure 7 (a) A cross-sectional SEM image of the ANF / ANF-g-SSNa membrane shows that the membrane thickness is only about 9.34 μm. A magnified view of the ANF-g-SSNa layer reveals a more compact structure, which helps to effectively block the polyiodide shuttle effect. Meanwhile, the other side retains the loose, porous structure of the original ANF membrane. This design not only facilitates rapid electrolyte penetration and ion transport but also provides a smoother diffusion path for zinc ions, thus maintaining high capacity under high-rate conditions. Figure 7 (b) The elemental distribution image shown further reveals a bilayer structure, with the uniform distribution of Na and S elements in the upper layer confirming the presence of -SO3. -The groups are uniformly distributed in the ANF-g-SSNa layer. Due to the influence of the vacuum filtration preparation process, a small amount of grafted modified fibers have penetrated into the lower ANF matrix, but this local phenomenon has no adverse effect on the overall performance of the separator. Although the introduction of the ANF-g-SSNa layer increases the functionality of the separator, its overall thickness remains at a relatively low level, which is crucial for reducing battery internal resistance and improving energy density in practical applications.
[0042] 3. Analysis of the reversibility of zinc deposition and nucleation kinetics Figure 8 The image shows the SEM morphology of the zinc anode after cycling, clearly revealing the regulatory effect of different membranes on zinc deposition behavior. When using an ANF membrane, the zinc sheet surface is covered with a large number of irregular needle-like or moss-like deposits, such as... Figure 8 (a) exhibits typical disordered two-dimensional diffusion characteristics, easily inducing zinc dendrite growth, which is a major cause of battery short circuits or failures. In contrast, zinc sheets using ANF-g-SSNa separators form a dense, lamellar, and uniformly oriented deposition structure on their surface, such as... Figure 8 (b) indicates that zinc ions are deposited in an ordered three-dimensional diffusion mode, effectively suppressing dendrite formation and improving interfacial stability. The Janus membrane exhibits an asymmetric inducing effect on the zinc deposition morphology, such as... Figure 8 (c, d) The ANF side induces a transformation of zinc particles from a disordered moss-like structure to a regular spherical shape, indicating that the microenvironment at this interface becomes favorable for uniform nucleation and growth of zinc, while the ANF-g-SSNa side maintains its original lamellar deposition characteristics. This further confirms the key role of sulfonate groups in promoting ordered deposition. This asymmetric structure not only improves the deposition uniformity of the non-functionalized side through physical confinement effects but also achieves highly ordered deposition on the functionalized side through chemical regulation, thereby synergistically enhancing the overall stability of the zinc anode.
[0043] like Figure 9 As shown, X-ray diffraction (XRD) analysis of the zinc anode after cycling revealed that the zinc sheet with the ANF separator had the highest content of byproducts, mainly basic zinc sulfate, indicating severe corrosion and side reactions during cycling. In contrast, the impurity peaks in the zinc sheet diffraction pattern of the ANF-g-SSNa separator were significantly reduced, indicating that the sulfonate groups effectively suppressed electrolyte decomposition and zinc surface passivation, improving interfacial chemical stability. The XRD results of the zinc sheets on both sides of the Janus-type separator were highly consistent with its SEM morphology; not only were the impurity peaks on the ANF-g-SSNa side significantly reduced, but the content of byproducts on the ANF side was also significantly reduced. This phenomenon further confirms that although the Janus structure is only functionalized on one side, its overall interfacial regulation capability can synergistically improve the deposition environment on both sides, effectively suppressing the occurrence of side reactions in the entire battery system.
[0044] 4. Long-cycle stability test of separators The long-cycle stability of separators is critical to the service life of zinc batteries. To investigate the cycling stability of separators under different current density conditions, cycling tests under different constant current conditions were carried out. Figure 10 (a) shows the long-cycle curves of Zn / / Zn symmetric cells using ANF, ANF-g-SSNa and ANF / ANF-g-SSNa membranes at 1mA·cm -2 , 1mAh·cm -2 condition. The polarization voltage after the initial stable stage (i.e., the charge-discharge platform difference) is shown in Figure 10 (b). The ANF-g-SSNa system has the lowest polarization voltage, indicating that it has the smallest interface impedance and optimal zinc ion transport kinetics. The polarization voltage of ANF is close to that of the Janus-type separator, but the Janus-type one is slightly lower, which is consistent with the optimization effect of its asymmetric structure on interface ion distribution. This polarization voltage ranking (ANF-g-SSNa < Janus < ANF) verifies the key role of sulfonate groups in reducing nucleation barrier and promoting uniform deposition.
[0045] The cell using the ANF separator only operated stably for about 488 hours before short-circuit occurred, and the voltage curve dropped abruptly to zero. Combined with the foregoing analysis, this is attributed to the lack of functional groups to regulate the interface ion distribution, resulting in highly uneven zinc deposition and dendrites penetrating the separator to cause internal short circuit. The functionalized ANF-g-SSNa separator greatly improves the cycling stability, and the cell can operate stably up to 1798 hours. However, sudden change in polarization voltage occurs followed by rapid failure thereafter, indicating that during long-term cycling, the separator may gradually lose mechanical integrity under repeated swelling / dehydration and electrochemical stress, leading to collapse or local rupture of the microporous structure, and eventually resulting in interface out of control. In contrast, the Janus-type ANF / ANF-g-SSNa separator exhibits the optimal long-cycle stability, and the cycling life of the cell reaches more than 2400 hours. Slight fluctuation of polarization voltage occurs after 2300 hours, but no immediate failure, as shown in Figure 10 (c), indicating that the separator can still maintain high interface stability and mechanical strength during long-term operation.
[0046] To compare with commercial separators, the cycling stability of glass fiber (GF) separators was also tested. As shown in Figure 11 , at 1mA·cm -2 , 1mAh·cm -2Under certain conditions, the Zn / / Zn symmetric cell assembled with the GF separator experienced a short circuit after only about 230 hours of stable operation, and its cycle life was significantly lower than that of the functionalized ANF-based separator system developed in this work. This result indicates that traditional commercial separators are significantly insufficient in suppressing zinc dendrites and maintaining interfacial stability, making it difficult to meet the application requirements of long-life aqueous zinc batteries.
[0047] At 2 mA·cm -2 2 mAh·cm -2 Cyclic tests were conducted on Zn / / Zn symmetric cells assembled with GF, ANF, ANF-g-SSNa, and Janus-type ANF / ANF-g-SSNa separators under the specified conditions. Figure 12 As shown in (a), as expected, the cycle life of all systems decreased at higher current densities. However, the Janus-type membrane still exhibited the best durability, operating stably for over 1400 hours. In contrast, the commercial GF membrane, pure ANF, and ANF-g-SSNa membrane experienced short circuits at approximately 100 hours, 318 hours, and 778 hours, respectively. Figure 12 As shown in (b), the cycle stability is significantly lower than that of the Janus-type ANF / ANF-g-SSNa separator. This indicates that even under higher current / higher areal capacity conditions, the ANF / ANF-g-SSNa separator, thanks to its asymmetric functional design, can still effectively suppress dendrite growth and maintain interface stability, highlighting its application potential in practical batteries.
[0048] Figure 13 The study demonstrated Zn / / Zn symmetric cells using different separators in multiple current density steps (0.5-1-2-4-8-1 mA·cm⁻¹). -2 Voltage-time curves under testing. Zn / / Zn cells using functionalized ANF-g-SSNa separators and Janus-type ANF / ANF-g-SSNa separators at up to 8 mA·cm⁻¹. -2 It can still operate stably at current densities of 1 mA·cm⁻¹ and return to normal operation at 1 mA·cm⁻¹. -2 After continuous cycling for over 180 hours, no short circuit was observed. In contrast, commercial GF and pure ANF membranes showed performance at 4 mA·cm⁻¹. -2 and 8 mA·cm -2 A short circuit occurred during the test. This demonstrated that introducing sulfonate groups significantly improves the interfacial stability and anti-dendrying ability of the membrane under high-rate conditions. Furthermore, the ANF / ANF-g-SSNa membrane achieves excellent dynamic cycling performance by balancing ion regulation and mechanical stability through asymmetric design.
[0049] The current density and surface capacitance were increased to 5 mA·cm⁻¹ -2 2.5mAh·cm -2Long-cycle tests were conducted at high magnification, such as... Figure 14 As shown in (a), the ANF / ANF-g-SSNa membrane also achieved the longest cycle life. Meanwhile, the difference between the ANF membrane and the ANF-g-SSNa membrane decreased, with short circuits occurring at 300 h and 370 h, respectively. This indicates that when the current density and deposition amount are significantly increased, the zinc ion flux increases sharply, and the interfacial concentration polarization intensifies, even with the introduction of -SO3. - Functional groups, whose regulatory capabilities tend to saturate, become the dominant factors in determining the membrane's mechanical strength, pore structure stability, and overall resistance to dendrite penetration. The ANF / ANF-g-SSNa membrane, with its asymmetric design—functional side guiding uniform nucleation and non-functional side providing structural support—effectively delays failure even under high loads, highlighting its comprehensive advantages.
[0050] Figure 14 (b) It was demonstrated that the battery using the Janus-type ANF / ANF-g-SSNa separator maintained stable operation during cycling at 740–840 h. However, when the current density and areal capacity were further increased to 10 mA·cm⁻¹, the performance declined. -2 and 5 mAh·cm -2 At times, such as Figure 14 As shown in (c), the cycle life of all systems was significantly shortened. Both ANF and ANF-g-SSNa membranes exhibited a polarization abrupt change and rapid failure after approximately 160 hours, while the Janus-type ANF / ANF-g-SSNa membrane also showed polarization runaway after approximately 210 hours. This result further emphasizes that even with optimized membrane design, the mechanical strength and interfacial stability of membranes still need to be further improved under extremely high-rate conditions.
[0051] 5. Inhibition of polyiodine shuttle by the diaphragm To verify the actual inhibitory effect of the functionalized membrane on the shuttle effect of polyiodine substances, a visualized iodine shuttle experiment was conducted using a U-shaped electrolytic cell, such as... Figure 15As shown in the image, the left side contains a brown cathode electrolyte with 0.1 M I₂ and 0.5 M ZnI₂, the right side contains deionized water, and different membranes are used as barrier layers in the middle. Optical photographs show that after 24 hours, both the commercial GF membrane and the pure ANF membrane exhibit significant brown staining on the right side of the electrolyzer, indicating that iodine has passed through the membrane and diffused into the right-side cell. This is attributed to the lack of functional groups in both the GF and ANF membranes that can effectively block iodine. The GF membrane showed more severe staining on the right-side cell after 12 hours, and the color was darker than that of the ANF membrane after 24 hours. This is because the GF membrane has a larger pore size, which cannot effectively block the shuttle of iodine through physical restriction; while the ANF membrane, although with a smaller pore size, is still insufficient to completely prevent the diffusion of iodine. In contrast, the ANF-g-SSNa membrane containing sulfonate groups and the Janus-type ANF / ANF-g-SSNa membrane did not show significant color changes in the right-side cell after 24 hours, indicating that the functionalized membranes significantly inhibited the shuttle of polyiodine through electrostatic interactions. Proved -SO3 - The electrostatic interaction with iodine effectively reduces its migration rate, thereby significantly reducing the transmembrane diffusion of iodine.
[0052] Figure 16 This study visually elucidates the regulatory mechanism of different membrane architectures on the polyiodide shuttle effect. Commercial GF membranes and the original ANF membranes, lacking functional groups, cannot construct an effective ion sieving barrier and therefore have almost no blocking ability for polyiodide species. Although this open structure does not restrict Zn... 2+ The migration of Zn leads to serious side reactions. In contrast, while the ANF-g-SSNa membrane with the introduction of sulfonate groups significantly inhibits the transmembrane diffusion of polyiodides through electrostatic repulsion, its dense functionalized layer inevitably induces a pore blockage effect, thereby increasing the diffusion rate of Zn. 2+ The transport resistance is high. However, the Janus-type ANF / ANF-g-SSNa membrane achieves synergistic performance optimization through a unique asymmetric structural design. It not only maintains the highly efficient barrier properties of the sulfonic acid group layer against polyiodides, but also constructs a layer on the other side that facilitates Zn transport. 2+ The fast-migrating, low-resistance channel achieves an ideal balance between suppressing the shuttle effect and ensuring ion conductivity.
[0053] like Figure 17 At 0.1 A·g -1After being fully charged at the current density and left to stand for 24 hours, the different systems exhibited significant differences: the GF and ANF films, lacking barrier capabilities, had low capacity retention rates of 63.1% and 59.2%, respectively, indicating that severe polyiodine shuttle during the resting period exacerbated the battery's self-discharge; the fully grafted ANF-g-SSNa film showed some improvement, but only reached 75.0%, possibly because the high concentration of polyiodides accumulated on the positive electrode side during the resting process created a large chemical potential difference with the negative electrode side. Due to the lack of low-resistance ion balance channels, this strong concentration gradient drove the polyiodides to slowly leak through microscopic defects or grain boundaries within the film, leading to capacity loss. In contrast, the Janus-type ANF / ANF-g-SSNa separator demonstrated excellent anti-self-discharge performance, with a capacity retention rate as high as 94.1%. This result strongly demonstrates that the Janus structure can not only effectively block the chemical diffusion of polyiodides but also maintain a good ion transport environment, thereby minimizing the loss of active materials.
[0054] like Figure 18 As shown in (a), at a low current density (0.2 A·g), -1 At high rates (4 A·g), the ANF-g-SSNa membrane battery exhibits excellent specific capacity, significantly outperforming both ANF and GF membranes. This is primarily attributed to its superior polyiodide barrier properties, which greatly enhance the utilization rate of the active material. However, as the current density increases to high rates (4 A·g), the specific capacity decreases. -1 The specific capacity of this battery exhibited a sharp decline, even falling below that of the GF and ANF films. This phenomenon confirms that the narrow pore size caused by the high grafting ratio is indeed a limiting factor for Zn. 2+ The bottleneck of rapid migration. In contrast, the ANF membrane battery exhibits a significantly higher specific capacity at low current densities than the commercial GF membrane. This indicates that its unique nanofiber network structure can suppress polyiodide shuttle to some extent through physical barrier effects, thereby improving the initial capacity of the battery. At high rates, its capacity retention is comparable to that of the GF membrane. This demonstrates that although the ANF membrane, as a non-functionalized separator, is not as thorough in suppressing the shuttle effect as functionalized membranes, its open pore structure ensures good ion permeability, allowing it to maintain transport kinetics comparable to commercial separators at high rates, without exhibiting significant ion transport resistance.
[0055] It is precisely based on the synergistic integration of the advantages of the two mechanisms mentioned above that the Janus-type ANF / ANF-g-SSNa separator exhibits superior overall electrochemical performance. Thanks to the efficient barrier effect of its functionalized layer, this separator-based battery achieves the highest specific capacity (197.3 mAh·g⁻¹) even at low current densities. -1 Even in 4 A·g -1 Even at high rate capability, its specific capacity can still reach 98.2 mAh·g.-1 This significantly outperforms all other comparative systems. This strongly demonstrates that the Janus asymmetric structure successfully resolves the contradiction between the grafted membrane's pores blocking zinc ion migration and the inability of the ungrafted membrane to effectively block polyiodine substances. Furthermore, Figure 18 (b) Further, the first-cycle constant current charge-discharge (GCD) curves of the ANF / ANF-g-SSNa membrane battery under different current densities are shown. The flat voltage plateau and stable curve shape once again confirm the excellent reaction reversibility and kinetic characteristics of the system.
[0056] like Figure 19 As shown, at a low current density (0.1 A·g), -1 Under these conditions, reaction kinetics are less restricted, and the ability to inhibit the shuttle passage of polyiodine substances becomes the key factor determining lifetime. At this point, the fully grafted ANF-g-SSNa membrane, thanks to its strong electrostatic repulsion, achieved an ultra-high capacity retention of 92.5% after 250 cycles. In contrast, the ANF and GF membranes, unable to block shuttle passage, failed rapidly at the 50th and 125th cycles, respectively. The Janus membrane maintained a capacity retention of 74.8% under these conditions, slightly lower than the ANF-g-SSNa membrane. This may be attributed to the fact that the synergistic effect between the ion transport channels and the barrier layer in its asymmetric structure has not yet reached optimal matching at extremely low flow rates, but its stability is still significantly better than that of traditional membranes.
[0057] However, when the current density is increased to 1 A·g -1 At times, such as Figure 20 As shown, the structural shortcomings of the ANF-g-SSNa membrane are clearly exposed. Limited by the high ion transport resistance and mechanical property loss caused by the dense functional layer, the battery assembled with the ANF-g-SSNa membrane fails in less than 1000 cycles, with a cycle life even comparable to that of the unmodified ANF membrane (both fail at a similar number of cycles). This indicates that under high-flux requirements, simple chemical modification, if sacrificing ionic conductivity and mechanical properties, cannot maintain long-term cycle stability. Similarly, the GF membrane also fails early due to its inability to suppress shuttle.
[0058] In stark contrast, the Janus-type ANF / ANF-g-SSNa separator exhibits excellent long-cycle durability. During a test lasting 3000 cycles, the battery operated smoothly, maintaining a capacity retention of 81.9%. This result strongly demonstrates that the Janus asymmetric structure successfully achieves a perfect balance between efficient multi-iodine barrier and rapid ion transport, providing an ideal solution for long-life operation of zinc-iodine batteries across a wide current density range.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a Janus diaphragm made of sulfonate-grafted modified aramid nanofibers, characterized in that, Includes the following steps: S1. Preparation of an aqueous dispersion of aramid nanofibers, including the following steps: S11. Disperse poly(p-phenylene terephthalamide) in a mixture containing dimethyl sulfoxide, KOH, and deionized water; stir to form a concentration of 2 mg / ml. -1 A uniform, deep red ANF / DMSO dispersion; S12. Add deionized water as a proton donor to the ANF / DMSO dispersion and continue stirring for 1 hour to complete the deprotonation reaction. S13. The mixed solution obtained from the deprotonation reaction is subjected to vacuum-assisted filtration to obtain a mixed gel. S14. Repeatedly add ethanol and deionized water to the mixture gel for washing and filtration to purify the mixture gel. S15. Redisperse the purified gel in deionized water under stirring, and adjust the concentration to 2 mg / ml. -1 A stable ANF aqueous dispersion, namely aramid nanofiber aqueous dispersion, was obtained. S2. The aramid nanofiber aqueous dispersion prepared in S1 is mixed with sodium p-styrene sulfonate, an initiator, and a reducing agent, and subjected to a free radical polymerization grafting reaction under anaerobic conditions. After washing and redispersing, a modified dispersion is obtained; including the following steps: S21. Take the aqueous dispersion of aramid nanofibers, remove most of the water by vacuum filtration, and obtain ANF colloid; S22. Transfer the ANF colloid to a light-proof container, and add the reducing agent, initiator, and sodium p-styrene sulfonate monohydrate in sequence; the initiator is ammonium persulfate, and the reducing agent is sodium bisulfite; S23. Place the light-proof container in a vacuum drying oven and repeatedly evacuate and purge with nitrogen three times or more to completely remove oxygen. After sealing, stir in a water bath at 50~60℃ and perform the grafting reaction for 2~6 hours to obtain the crude product ANF-g-SSNa. S24. The crude ANF-g-SSNa product was washed multiple times with a large amount of deionized water, and then ultrasonically redispersed to adjust the concentration to 2 mg / mL. -1 A stable ANF-g-SSNa aqueous dispersion, i.e., modified dispersion, was obtained. S3. Using a sequential vacuum filtration method, the modified dispersion obtained in S2 is first filtered to form a membrane, creating the first layer; then, the aramid nanofiber aqueous dispersion obtained in S1 is further filtered onto the first layer to form the second layer; after drying and peeling, the sulfonate-grafted modified aramid nanofiber Janus membrane is obtained; including the following steps: S31. Mix the modified dispersion with deionized water, ultrasonically disperse for 10 min, pour into a vacuum filtration device, and vacuum filter to form an ANF-g-SSNa layer. S32. Mix the aramid nanofiber aqueous dispersion with deionized water, ultrasonically disperse for 10 minutes, and then pour it into the filtration device described in S31. Continue filtration above the ANF-g-SSNa layer to form an ANF layer. After vacuum filtration is completed, a composite membrane is formed. Take the composite membrane and the filter membrane out of the filtration device together. S33. After drying the composite membrane together with the filter membrane under vacuum at 60°C for 12 hours, the filter membrane is peeled off to obtain the ANF / ANF-g-SSNaJanus membrane, namely the sulfonate grafted modified aramid nanofiber Janus membrane.
2. The method for preparing a Janus diaphragm modified with sulfonate grafting according to claim 1, characterized in that, In S11, the ratio of poly(p-phenylene terephthalamide): dimethyl sulfoxide: KOH: deionized water is 1g: 500ml: 1.5g: 20ml.
3. The method for preparing a sulfonate-grafted modified aramid nanofiber Janus membrane according to claim 1, characterized in that, In step S22, the mass ratio of sodium styrene sulfonate monohydrate to the aramid nanofibers in the aramid nanofiber aqueous dispersion taken in step S21 is (1~5):
1.
4. The method for preparing a sulfonate-grafted modified aramid nanofiber Janus membrane according to claim 1, characterized in that, The mass ratio of the initiator to the aramid nanofibers in the aqueous dispersion of aramid nanofibers taken in S21 is (0.1~1):1, and the mass ratio of the reducing agent to the aramid nanofibers in the aqueous dispersion of aramid nanofibers taken in S21 is (0.5~1.5):
1.
5. The method for preparing a sulfonate-grafted modified aramid nanofiber Janus membrane according to claim 1, characterized in that, The volume ratio of the modified dispersion taken in S31 to the aramid nanofiber aqueous dispersion taken in S32 is 1:(1~2.5).
6. The sulfonate-grafted modified aramid nanofiber Janus separator prepared by the method described in any one of claims 1-5 is used to prepare a zinc-iodine battery.
Citation Information
Patent Citations
Functional aramid nanofiber coated diaphragm as well as preparation method and application thereof
CN118448806A